The Workforce Field Challenges in the Light of the New Developments of AI - Roxana Matefi (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
Artificial intelligence and its development continue to be some hot topics nowadays due to the continuous challenges that they involve. While many are fascinated by AI’s accelerated pace of development and embrace the new technologies wholeheartedly, others seem to be more resistant and reluctant and tend to concentrate mainly on its disadvantages. This article deals with the challenges faced by the European workforce field in the context of the increasing developments of AI.